(untitled) (Bulletin of criminological association of Ukraine, 2024)
The article presents the results of its own research into the category of violent crime of persons with psychical anomalies within the limits of sanity and an analysis of the reasons and conditions that contribute to the commission of these criminal offenses. It was determined that clarifying the reasons and conditions for committing violent crimes, where the subject of the commission is a person with psychical anomalies within the limits of sanity, is important for further activities related to their prevention and prevention. It is emphasized that psychical anomalies can have criminogenic and social significance, but they can’t be a direct cause of criminal behavior. Attention is focused on the fact that mental anomalies are internal, subjective conditions, that is, the ground on which, under unfavorable social circumstances, antisocial intentions more easily arise and are realized. It was concluded that psychical anomalies alone can’t fully explain some reasons for committing crimes. It has been proven that the causes and conditions of violent crimes committed by persons with psychical anomalies are set of material, ideological, socio-demographic and other factors existing in our society today, under the influence of which a certain category of persons, and especially those with psychical anomalies, antisocial views and habits are approved, and on this basis, a criminal intention is formed and implemented.